Zero budget natural farming: A promising model in Indian agriculture - Om, Hari; Vijay, Vijay; Singh, Baljeet (Indian Farming, 2019)
On the basis of initial investigations and observations at 180 acres of Gurukul Farm Kurukshetra, it appears that Zero Budget Natural Farming (ZBNF) may be a promising model in Indian Agriculture. The analytical results from different institutions (CCS HAU, Hisar; PAU Ludhiana, IIFSR Modipuram and Kurukshetra University Kurukshetra) have reflected that there was incredible enrichment of soils in terms of organic carbon (OC), available phosphorus, available potash, micronutrients and biological health. The results indicated that the average OC in the soil samples collected from Gurukul farm in June 2017 and analyzed at CCS HAU, Hisar and IIFSR, Modipuram was 0.61 and 0.62%, respectively. Around 19 and 30% soil samples in the analysis of IIFSR and CCS HAU were found sufficient/rich in OC (>0.75%). After one year of cropping i.e. in June 2018, soil samples were again collected and analysed at CCS HAU Hisar. It was observed that 95% soil samples were rich in OC with average OC value of 0.91% in the range of 0.82-1.12%. For confirmation of results, soil samples were further drawn in October 2018 after kharif and analyzed at CCS HAU, Hisar and PAU, Ludhiana. These results indicated that the average OC was 0.84 and 0.78% in the soil analysis reports from the respective institutes. The increase in OC by 49% (from 0.61 to 0.91%) in a period of only one year and the maintenance of average OC at the level of more than 0.75% across the season on a farm of 180 acres exhibit the impact of ZBNF practices. Seasonal variation and crop management practices may exert influence on OC content of soil.